Laparoscopic liver resection for liver tumours in proximity to major vasculature: A single-center comparative study. Issue 4 (April 2020) - D'Hondt, Mathieu; Willems, Edward; Parmentier, Isabelle; Pottel, Hans; De Meyere, Celine; Vansteenkiste, Franky; Besselink, Marc G.; Verslype, Chris
Abstract: Background: With growing popularity and experience in laparoscopic liver surgery, the options for more difficult procedures increase. Only small case series have been published regarding laparoscopic liver resection (LLR) for tumours in proximity to major vessels (MVs). The aim was to compare outcomes of LLR for tumours located less or more than 15 mm from MVs. Methods: This was a retrospective analysis of a prospectively collected database of consecutive LLR (October 2011–August 2017). Proximity to MVs (PMV) was defined as lesions located within 15 mm to the caval vein, hepatic veins and portal vein (main trunk and first branches). The control group were all lesions located more than 15 mm from MVs. Results: Some 60/235 LLR were performed for lesions in proximity to major vasculature (24%). In the PMV group, median IWATE Difficulty Score was higher (8.5 (IQR: 6.0–9.0) VS 5.0 (IQR: 3.0–6.0), p < 0.001) as was the use of CUSA® (45.0% VS 8.6%, p < 0.001) and Pringle manoeuvre (8.3% VS 1.7%; p = 0.028). Operative time was longer (180min (IQR: 140–210) VS 120min (IQR: 75–150), p < 0.001) and blood loss was higher (190 ml (IQR: 100–325) VS 75 ml (IQR: 50–220), p < 0.001) in the PMV group. There was no difference in perioperative blood transfusion (3.3% VS 1.7%, p = 0.60) or postoperative morbidity (15.0% VS 14.3%, p = 0.89). There was no mortality in both groups. On mean follow-up of 21 months, no significant differences could be found in disease free (p = 0.77) and overall survival (p = 0.12). Conclusion: In experienced hands, LLR of lesions in proximity to MVs is safe and feasible with acceptable short and long-term results.